Pemberhentian Jaksa Agung dan Hak Prerogatif Presiden - Riri Nazriyah (Jurnal Konstitusi, 2016)
The rules of appointment and dismissal for the attorney generals  need to be regulated concretely in the law. It was not done solely by President but must be on the consideration of Parliament. Therefore, the implementation of its truly free from interference and political interests   of President. Term of office of the of the Attorney General should be established with certainty to avoid multi-interpretations that would lead to legal uncertainty.